INCIDENCE OF Tuthillia cognata (Hodkinson) IN FOLIAR SPROUT OF 43 PROGENIES OF Myrciaria dubia-Myrtaceae, IN LORETO - PAREDES DÁVILA, Elvis Javier (2018)
The plagues in the camu camu, are manifested in the different productive stages, not being an exception in the nursery and in the initial plantation, leading to a decrease in productivity over time. The objective in this work was to determine the incidence of Tuthillia cognata, in foliar shoots of camu camu plants of 3 years of sowing in final field, to know the potential of resistance or susceptibility within a genetic test of 43 progenies. The number of foliar sprouts / plant and the percentage of leaf shoots with damage by T. cognata were evaluated. Variance analysis and statistical tests were performed on means of data (Tukey and Scott & Knott at 5% probability). Statistical differences in the variance between progenies (p≤0.05) were determined for "number of leaf shoots" and "percentage of leaf shoots with damage". Evidencing that the plants with the highest number of leaf buds emitted do not present the greatest damage due to the plague studied, other factors (genetic and physiological) may possibly exist between progenies that cause the phenotypic manifestation of the variables to be different in each case. its resistance or susceptibility to the plague. According to resistance to T. cognata, clone 48 and 02-15-05 with 0% of damaged leaf buds, in addition to the progenies 15-14-07, 06-15-09, clone 29, and 15-06, stood out. -13 with values lower than 2.5%. By contrast, greater susceptibility was observed in progenies 15-04-8, 14-11-7,